AME annual conference the renaissance of public services, 29-30 June 2000, Edinburgh International Conference Centre, UK : speakers' papers. (Thomas Telford, 2000)
Providing access to engineering content from the past, this is the proceedings of the Association of Municipal Engineers' annual conference held in 2000.
Keywords: Municipal engineering -- Congresses.; elektronické knihy; electronic books